Integrated Nutrient Management of an Acid Paddy Soil in Karang Tanjung Village, Padang Ratu, Central Lampung - Kasno, Antonius; Irawan, Irawan; Husnain, Husnain; Rochayati, Sri (UNIVERSITY OF LAMPUNG, 2017)
Balanced fertilization is the key factor to improve the efficiency and effectiveness of fertilization.The dosage of inorganic fertilizers applied can be determined based on the nutrient status of P, K and rice productivity. The research aims to improve balance fertilization that combines inorganic fertilizers, which is set up based on soil nutrient status, and organic fertilizers. The research was conducted in Karang Tanjung Village, Padang Ratu District, Central Lampung, in the dry season of 2009 until 2012. An experimental plot of one hectare was set up in the farmerâ€™s paddy fields. Generally, the plot for every treatment was owned by two or more farmers. The treatments consisted of the dose of fertilizer applications for lowland rice, namely (1) dose of fertilizers based on farmer practice, (2) dose of fertilizers proposed by Petrokimia, (3) 75% of fertilizer dose that was set up based on soil analysis plus straw compost, and (4) 75% of inorganic fertilizer combined with manure and biofertilizer. At the fourth growing season, each plot was applied with 100% inorganic fertilizer (NPK fertilizer). The results showed that the limiting factor of the soil used in the current study is the content of organic-C, N, K, and CEC. The compost of rice straw used as organic matter in the current study contains higher organic-C and total-N in comparison to manure. Organic matter application in the form of straw compost or manure can reduce 25% of NPK application, while the production of rice remains high. Fertilization on paddy soils based on soil nutrient status can improve fertilization efficiency. Rice production in the treatment of 100% NPK is similar to that in the fertilization treatments based on farmer practice and Petrokima rate.Â Keywords: Nutrient management, acid soil, fertilization efficiency